Influence of Superstructure Slenderness on the Fragility Curves of Buildings with ADAS, TADAS, and SLB Dissipaters - Julcarima Espiritu, Abel Max (2025)
This study evaluates the influence of structural slenderness on the seismic response of buildings equipped with ADAS, TADAS and SLB hysteretic dissipaters. Structures with three levels of slenderness (1, 2 and 3) were modeled and analyzed by means of static and dynamic nonlinear analysis simulations. To quantify structural vulnerability, fragility curves were generated considering Immediate Occupancy, Life Safety and Collapse Prevention performance states as a function of peak ground acceleration (PGA). The results show that the incorporation of dissipaters significantly reduces the inelastic demand and delays the appearance of critical performance states, even in buildings with greater slenderness. However, differences were identified in the effectiveness of each type of dissipator depending on the geometric configuration. In less slender structures, the dissipaters maintained low probabilities of critical damage up to high PGA. On the other hand, in more slender buildings, seismic vulnerability increased significantly above 0.50g, with a higher probability of reaching Life Safety and Collapse Prevention states. The SLB dissipater presented the most uniform performance in all configurations, significantly reducing the probability of severe damage. In contrast, the ADAS and TADAS dissipaters showed a progressive reduction in their damage mitigation capacity as structural flexibility increased, thus increasing the probability of reaching critical performance states. These findings highlight the importance of adjusting the mechanical properties of dissipaters according to structural slenderness to optimize seismic response. The exploration of advanced strategies, such as the combination of multiple dissipaters and the consideration of geometric variations and soil conditions, is recommended in order to improve structural resilience to large magnitude seismic events.